X-ray absorption near-edge structure study on the configuration of Cu2+/histidine complexes at different pH values*Project supported by the National Natural Science Foundation of China (Grant No. 11205186). (25th February 2016) - Yu 于, Mei-Juan 梅娟; Wang 王, Yu 宇; Xu 徐, Wei 伟
Abstract: The local configurations around metal ions in metalloproteins are of great significance for understanding their biological functions. Cu 2+ /histidine (His) is a typical complex existing in many metalloproteins and plays an important role in lots of physiological functions. The three-dimensional (3D) structural configurations of Cu 2+ /His complexes at different pH values (2.5, 6.5, and 8.5) are quantitatively determined by x-ray absorption near-edge structure (XANES). Generally Cu 2+ /His complex keeps an octahedral configuration consisting of oxygen atoms from water molecules and oxygen or nitrogen atoms from histidine molecules coordinated around Cu 2+ . It is proved in this work that the oxygen atoms from water molecules, when increasing the pH value from acid to basic value, are gradually substituted by the Ocarboxyl, Nam, and Nim from hisitidine molecules. Furthermore, the symmetries of Cu 2+ /His complexes at pH 6.5 and pH 8.5 are found to be lower than at pH 2.5.